2013
DOI: 10.1128/iai.00268-13
|View full text |Cite
|
Sign up to set email alerts
|

Altered Innate Defenses in the Neonatal Gastrointestinal Tract in Response to Colonization by Neuropathogenic Escherichia coli

Abstract: d Two-day-old (P2), but not 9-day-old (P9), rat pups are susceptible to systemic infection following gastrointestinal colonization by Escherichia coli K1. Age dependency reflects the capacity of colonizing K1 to translocate from gastrointestinal (GI) tract to blood. A complex GI microbiota developed by P2, showed little variation over P2 to P9, and did not prevent stable K1 colonization. Substantial developmental expression was observed over P2 to P9, including upregulation of genes encoding components of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 77 publications
1
69
1
Order By: Relevance
“…The bacteria are ingested, colonize the GI tract, translocate into the blood compartment via the mesenteric lymph nodes before establishing organ-specific disease with associated inflammation of the brain 24 . Importantly, the model displays strong age dependency; as shown in Figure 3, two-dayold (P2) rat pups are highly susceptible to invasive disease but over a seven-day period the animals become progressively more refractory to infection, but not to GI tract colonization 17 . After transit from the site of GI colonization to the blood compartment, the bacteria can be visualized in blood samples by fluorescence microscopy (Figure 4) before entering the CNS predominantly at the choroid plexus 25 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacteria are ingested, colonize the GI tract, translocate into the blood compartment via the mesenteric lymph nodes before establishing organ-specific disease with associated inflammation of the brain 24 . Importantly, the model displays strong age dependency; as shown in Figure 3, two-dayold (P2) rat pups are highly susceptible to invasive disease but over a seven-day period the animals become progressively more refractory to infection, but not to GI tract colonization 17 . After transit from the site of GI colonization to the blood compartment, the bacteria can be visualized in blood samples by fluorescence microscopy (Figure 4) before entering the CNS predominantly at the choroid plexus 25 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…The pups rapidly develop a complex microbiota and within two days of birth the GI tract is colonized with a wide range of bacteria from the phyla established as the most abundant microbes in the infant and adult gut. Pups that have not been fed E. coli A192PP do not carry E. coli K1 in the GI tract 17 and so determination of rates of colonization is relatively straightforward. However, the neuS-based qPCR method for detection of colonizing E. coli K1 is far more sensitive that traditional culture methods and is strongly recommended 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of previous investigations have shown that different inflammatory factors may contribute to the pathogenesis of intestinal barrier injury, and most studies have focused on the pathological roles of cytokines and biologically active mediators produced by enterocytes and macrophages 13,14 . However, the relationships between vasoregulation and the protective mechanisms of the gastrointestinal barrier have not been investigated.…”
Section: Ijpsr (2017) Volume 8 Issue 7 (Research Article)mentioning
confidence: 99%
“…The protective function of the intestinal mucosal barrier depends on the expression and properties of mucins 8 and antimicrobial defensive factors, which are involved in the regulatory system and generate the main chain of host defence against pathogens 9 . Mucins are actively expressed in the epithelium of the gastrointestinal tract and form the high-molecularweight viscoelastic layer, which is the protective barrier between the mucosal surface of the abdominal contents of the gastrointestinal tract, representing a nourishing environment for vital activity of commensal bacteria of the intestine 10,11 .…”
Section: Ijpsr (2017) Volume 8 Issue 7 (Research Article)mentioning
confidence: 99%